POLITICAL HEGEMONY AS A MEDIA OF DA’WAH MUHAMMAD BIN ABDUL WAHAB - Ms Udin; Irpan Irpan (UIN Mataram, 2021)
Da'wah is an activity that is inherent in humans, especially for a Muslim or Muslimah. In this study, the researcher describes Muhammad Bin Abdul Wahab's da'wah method using political media as a propaganda medium, namely by collaborating with the head of state Ibn Saud who has the same expansion interests, namely regional expansion (Ibn Saud) and teaching expansion (Muhammad Bin Abdul Wahab). Before making the collaborating, Muhammad Bin Abdul Wahab received the resistance from the community and even his own family, but after collaborating with Ibn Saud, Muhammad Bin Abdul Wahab's da'wah activities got a new spirit, especially Ibn Saud was a warlord so that Muhammad Bin Abdul Wahab's preaching space was wide open in the Arabic land.